Intestinal pseudoobstruction in acute Lyme disease - Chatila, Rajaa (1998)
We report here a case of acute Lyme disease in a 61-yr-old man who developed a facial nerve paralysis and a relentless intestinal pseudoobstruction 2 wk after the initial prodrome. Both the facial nerve paralysis and pseudoobstruction persisted for a month until the patient sought medical attention. Both lesions resolved only after treatment for Lyme disease was initiated. The temporal association of the pseudoobstruction with the somatic cranial neuropathy and the response of both to specific therapy for Lyme disease suggest that the former was likely the result of a reversible autonomic neuropathy or dysfunction.